Desarrollo de un manual de operación para el centro de purificación y refinación del centro de procesos e innovación (CEPIIS) de la Universidad de América. (2023)
This project was carried out in order to develop an operation manual for the purification and refining center of the process and innovation center (CEPIIS) of the University of America. Which includes identifying variables, parameters and operational safety aspects of the equipment, establishing the operating procedures based on the information provided by the suppliers, integrating with other CEPIIS teams that can provide relevant information on the equipment. , update the information in the manual from guides and equipment manuals with potential application and finally develop the central structure of the operation manuals, for their subsequent construction.